Privacy in smart speakers: A systematic literature review. Issue 1 (17th October 2022) - Maccario, Guglielmo; Naldi, Maurizio
Abstract: Parallel to the increasing use of smart speakers (aka virtual assistants), privacy concerns emerge. In this article, we provide a systematic review of the literature on privacy issues in smart speakers. Both Scopus and Web of Science databases are examined, as well as the preprint repository arXiv, to take into account the most recent contributions. That literature exhibits a continuously growing trend in the last 4 years, with the USA being the single largest contributor to the field. The topics debated in the literature concern the perception of privacy issues, their contribution to adoption choices, the identification of vulnerabilities, the proposal of possible countermeasures, and (last and least) the analysis of the legal cases that are arising.